Automated scheduling of hostel room allocation using genetic algorithm - Rayner Alfred; Hin, Fuk Yu (2020)
Due to the rapid growth of the student population in tertiary institutions in many developing countries, hostel space has become one of the most important resources in university. Therefore, the decision of student selection and hostel room allocation is indeed a critical issue for university administration. This paper proposes a hierarchical heuristics approach to cope with hostel room allocation problem. The proposed approach involves selecting eligible students using rank based selection method and allocating selected students to the most suitable hostel room possible via the implementation of a genetic algorithm (GA). We also have examined the effects of using different weight associated with constraints on the performance of the GA. Results obtained from the experiments illustrate the feasibility of the suggested approach in solving the hostel room allocation problem.